NILAI-NILAI PENDIDIKAN AKHLAK DALAM KISAH AISYAH R.A PADA BUKU SULAIMAN AN-NADAWI DAN RELEVANSINYA TERHADAP PENDIDIKAN AKHLAK ISTRI DI ERA MODERN - Agus Faisal Asyha; Waluyo Erry Wahyudi; Fenny Febrianti Pesawal (Jurnal Ilmiah AZZIQRI: Kajian Keislaman dan Kependidikan, 2024)
Abstract This research is motivated by the presence of moral deviations in Indonesian society, including theft, sexual misconduct, allegations, self-indulgence, and adultery. These issues highlight a decline in societal morals, which is concerning, especially among women who play a crucial role in Islamic upbringing. Women are seen as the backbone of Islamic values, as they are future mothers who will teach their children about Islam. The book "Aisyah The Most Beautiful Lover" by Sulaiman An-Nadawi is central to this research, offering numerous stories with moral educational values that serve as life guidance and motivation. It acts as a mirror for Muslim women to reflect on their lives, assess their spiritual state, and strive for self-improvement by emulating the life of Aisyah RA. Additionally, the book is valuable as teaching material for students to learn about Aisyah RA, the mother of the believers, thereby introducing young Muslims to her exemplary life. This research employs a library research method. The analysis of the book identifies three categories of moral education values: Morals towards Allah SWT: including faith in Allah, gratitude, wara' (piety), and fear of Allah; Morals towards others: including justice, generosity, patience, helpfulness, and obedience to one's husband; Morals towards oneself: including guarding one's tongue, safeguarding one's soul/self, humility (tawadhu'), contentment (qona'ah), and asceticism (zuhud).The research concludes that the moral values outlined in the book are relevant to modern life. These include fostering faith in Allah, gratitude, piety, fear of Allah, justice, generosity, patience, helpfulness, obedience to one's husband, guarding one's tongue, safeguarding one's soul, humility, contentment, and asceticism.